2009
DOI: 10.1080/10409280902783483
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Pathways in Early Childhood Professional Development: An Exploration of Early Educators in Public Preschools, Private Preschools, and Family Child Care Homes

Abstract: This paper presents a naturalistic investigation of the patterns of formal education, early childhood education training, and mentoring of a diverse group of urban early childhood educators participating in the Los Angeles: Exploring Children's Early Learning Settings (LA ExCELS) study. A total of 103 preschool teachers and family child care providers serving primarily low-income 3- and 4-year-old children in Los Angeles County provided data on their education, training, and beliefs about teaching. This sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 14 publications
1
28
1
2
Order By: Relevance
“…However, our analysis did not reveal any significant correlations. Furthermore, in contrast with Fuligni et al (2009), our analysis did not reveal any significant correlations between the demographic variables and teachers' PD needs in the different learning areas.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…However, our analysis did not reveal any significant correlations. Furthermore, in contrast with Fuligni et al (2009), our analysis did not reveal any significant correlations between the demographic variables and teachers' PD needs in the different learning areas.…”
Section: Discussioncontrasting
confidence: 44%
“…For example Fuligni et al (2009) found that PD focused on family child care allowed teachers to enhance their authoritative or democratic beliefs about children, whereas PD related to child development enhanced the positive emotional climate in the classroom. More recently, Hur et al (2015) have investigated the predictors of teachers' child-centered beliefs with a large sample of preschool educators in the United States.…”
Section: Teachers' Beliefs About Children and How They Learnmentioning
confidence: 99%
“…Context can include the ages of the children served (e.g., infants and toddlers versus preschoolers) and their home languages (Winton et al 2016;Zaslow et al 2010). Also to be considered are the programmatic inputs used (e.g., curriculum) and the availability of onsite mentoring to follow up on any training (Fuglini et al 2009;Howes et al 2003;Vu et al 2008). The extent to which there is a 'culture of learning' for teachers also appears to play a role (Ackerman 2007;Connors 2016).…”
Section: Alignment With Staff And/or Work Needsmentioning
confidence: 99%
“…We employed an empirically based understanding of the best practices within teacher education that have been correlated with teachers' pedagogical change to accomplish this task (Fulligni et al 2009;Webster-Wright 2009). The primary goals of the PD course included supporting, as well as challenging, these teachers' practices with culturally and linguistically talented children in a close and personal environment in which the researchers and teachers studied and worked together in the schools where they actually taught (Pultorak et al 2006).…”
Section: The Pd Course and Its Conceptual Frameworkmentioning
confidence: 99%